Edukasi Konseling Remaja Di SMK Negeri 4 Pandeglang dengan Pendekatan Mathematics Of Love Languages - Arfatin Nurrahmah; Solihatun; Endang Wiyanti; Nurhayati (PELITA NUSA TENGGARA, 2026)
Adolescent Counseling Education at SMK Negeri 4 Pandeglang Using the Mathematics of Love Languages Approach. Creating a supportive learning environment, where understanding students' communication styles and emotional needs can enhance the overall effectiveness of the teachinglearning process, is crucial and this extends beyond the realm of counseling. The community service program titled Adolescent Counseling Education at SMK Negeri 4 Pandeglang Using the Mathematics of Love Languagesaims to provide an innovative approach to building more positive communication and relationships between teachers and students. Through training comprising interactive workshops, simple numerical simulations based on love languages theory, and case discussions, teachers from various subjects were guided to map and understand their students' interpersonal characteristics. The evaluation results indicate the program's success, with highly positive feedback from participants. Specifically, 75% of teachers found the material easy to understand, 73.5% rated it as engaging and applicable, and 80.9% felt the facilitation team delivered the content with exceptional clarity. More importantly, 83.8% of participants acknowledged a significant increase in their understanding of teacher-student dynamics, and 82.4% felt motivated to apply these concepts in their daily interactions within the classroom and school environment. In conclusion, this training successfully introduced a practical and well-received framework, the implications of which can strengthen emotional bonds within the school community and, ultimately, support the achievement of educational goals more holistically.